Fulfillment of women's political rights through mainstreaming gender quotas in Election Supervisory Board - Muharam, Ricky Santoso; Pradhanawati, Ari; Fitriyah, Fitriyah; Supratiwi, Supratiwi (Department of Government Studies, Universitas Muhammadiyah Makassar, 2023)
This study examines women's political representation as election supervisors, the rules regarding women's representation in accordance with the regulations of Law Number 7 of 2017 concerning General Elections have not been able to run well. This study uses qualitative research by making observations in the recruitment process of the Election Supervisory Board of the Republic of Indonesia and the affirmation quota of women as election supervisors in Election Supervisory Board, Yogyakarta Special Region Province. This study aims to see the application of regulations on the general election law on women's representation and its application in the recruitment process of election supervisors that accommodate women's representation. This finding shows that there is still a gap in women's representation in election supervisory institutions where the rules regarding 30 percent female representation have been very clearly regulated. Evaluation of these findings requires a policy of changing regulations that regulate sanctions for non-fulfillment of women's representation as one of the solutions to fulfill women's gender kouta as female supervisors. The conclusion of this study is that there are several factors that hinder the fulfillment of women's political rights such as, a wrong understanding of political gender, the risk of becoming a very large election supervisor, socialization of selection that is not right on target and the competence of prospective candidates who lack knowledge about elections.